Inter-Decadal Dynamics of Glacier Area and Supra-glacial Lakes Over Hispar Glacier, Western Karakoram - Qureshi, Javed Akhter; Ali, Sajid; Khan, Garee; Bano, Iram; Hussain, Shabahat (International Journal of Economic and Environmental Geology, 2023)
Glaciers of the central Karakorum region are the primary source of fresh water and lifeline for downstream inhabitants but changing climatic conditions put serious impacts on glaciers which cause rapid ablation and the creation of glacial lakes. Many natural hazards are associated with glaciers and glacial lakes like Glacier lake outburst flood (GLOF). Using Geographic Information System and Remote sensing techniques on Hispar glacier which is part of central Karakorum, the current study applied Landsat (TM, ETM, ETM+, and OLI) and sentinel-2 satellite imagery. Further, mapping to the Hispar glacier is done to know the variations in glacier and supraglacial lakes between 1990 and 2019. According to the results, about 90% of glacial ponds are present in the debris-covered area while only 10% are present in the clean ice and scow area. This study identifies the decreasing trend in the number and the area of glacial lakes. In 1990, about 42 glacial ponds were covering a total area of 0.733km2, whereas, in 2019, 20 glacial lakes were covering an area of 0.18km2. In the last three decades (1990-2019) about 20km2 of clean ice and snow is increased. The findings of climate data revealed that there is a decreasing trend of temperature and an increasing trend of precipitation. Since 1995, about 0.75oC temperature is observed in HRB. The findings of this study somehow support the Karakoram anomaly.